Diálogos entre a equipe clínico-especializada e a escola sobre a educação inclusiva: tessitura de narrativas, saberes e práticas - Araújo, Luana Barreto de (2018)
This study aimed to analyze the main demands of knowledge (understanding, information) and practices that both school and a clinical-specialized team, in their respective contexts of action, present in regards to the met individuals, with possible reverberations in school inclusion. We also seek the identification and analysis of dialogue points and actions of integral attention. The research's conceptual framework contemplated two referential pillars: Health (TELLES, 2006; DIAS, 2016; BATISTA, 2008); and Education (LUSTOSA, 2009; 2015; 2018; MANTOAN, 2003; MITTLER, 2003; BOOTH; AINSCOW, 2012). In addition to this theoretical corpus, we worked with the notions of inter-epistemic practices (BORRI-ANADÒN, 2015), epistemology of knowledge (TARDIF, 2014), field and habitus (BOURDIEU, 1963; 1983; 1992; 1994; 2015) and core field (CAMPOS; CHAKOUR; SANTOS, 1997; CAMPOS, 2000). Methodologically, it was a qualitative research, in a comparative perspective (national and international literature) to draw a current overview of possible interfaces, with possibilities and/or fragilities of dialogues favoring individuals and their inclusive educational processes. We started from an outpatient clinic specializing in the care of children/adolescents with intellectual disabilities, autism spectrum disorders, mental and emotional disorders, among others. The data collection period was from May to September, 2018. The research stages were: documentary analysis coupled with medical records to collect information from the consultations and the individual’s demeanor (with a specific script); analysis of evaluation protocols and teacher’s reports required by the attendance team; in education, a survey was carried out in 30 schools of Fortaleza’s Municipal Network (survey and visits) on the interface between Health and Education. Schools with a greater number of students with disabilities were selected, based on the Report of Students with Disabilities by School Units of the Municipal Department of Education of Fortaleza. We proceeded to investigate content, classification and thematic categorization of information, at the intersection of these professional areas. The results showed that the school reports requested by the clinical-specialized team exclusively introduced the children through an array of problems and difficulties, in addition to expressly requesting reports (moreover, already indicating the type of disability of the intended child on the report). In general, they did not show potentialities, centers of interest and/or levels of development and learning of the students, nor did they materialize levels of school performance. It is clear that the methods demanded by the two areas are based on educational practices that surpass the quantitative character of evaluation protocols, school reports and intervention. There is a convergence between the core notions (professional categories) and field notions (inclusive practices), which is the necessary intersection zone between these areas. Furthermore, the potential for dialogue that needs to be fortified stands out, becoming a major goal for both areas, which are the inclusive practices based on integral attention, under the aegis of a qualified and expanded view on the individuals and their life contexts. It urges the materialization of interprofessional practices in favor of a collaborative effort that reach intersectoral status, not in function of a diagnosis, but in favor of an inclusion in school.